Eexpression of mRNA inos and mRNA eNOS in the liver of rats with chronic alcohol intoxication and with the introduction of achillea micranthoides klok herb extract. Et krytzka - Belenichev, I. F.; Duyun, I. F.; Kamyshnyi, O. M.; Mazulin, O. V.; Suprun, E. V.; Makyeyeva, L. V.; Бєленічев, Ігор Федорович; Дуюн, Ірина Федорівна; Камишний, Олександр Михайлович; Мазулін, Олександр Владиленович; Макєєва, Людмила Валеріївна (Czech Republic: European Scientific Center Biologial Marker, 2020)
A few studies have established that ethanol changes the activity and expression of NOS in target organs, leads to overproduction of NO and its cytotoxic forms [1,2]. All this causes the initiation of nitrosating stress, apoptosis, and changes immunocompetence. This is due to the nature of ethanol effect on various NOS isoforms. Some researchers have shown that ethanol increases the expression of iNOS, the trigger of nitrosative stress indirectly via the activation of IL-1b [3-5].
Keywords: experimental alcohol intoxication; iNOS mRNA; eNOS mRNA; yarrow hearth; Achillea micranthoides Klok; Et Krytzka